PRODUCTIVITY OF GEESE OF PARENT HERD WHEN USING FEED ADDITIVE «VETOSEL E FORTE» - Суханова, С. Ф.; Азаубаева, Г. С. (Scientific Progress & Innovations, 2017)
Researches established that use of feed additive «Vetosel E forte» for geese of parent herd in an optimum dosage of 0,6 ml/10 l of drinking water allowed to increase egg productivity by 2,15–10,40 %, safety for 0,47–1,68 %, an impregnation of eggs for 0,99–3,09 %, deductibility – on 5,81–11,02, a young growth conclusion – for 6,10–12,66 %. In case of its use more expressed tissue respiration, phagocytic activity, number and index is noted also 2,82 % increased by 4,34 %, 10,28 (Р≤0,05). The daily gooses received from experimental gooses differed in higher nonspecific immunity. Due to use of «Vetosel E forte» a forage expense on 1000 pieces of eggs decreased by 2,26–12,84 %, and the level of profitability of production of incubatory goose eggs increased by 1,98–4,74 %.